2022
DOI: 10.1017/eds.2022.22
|View full text |Cite
|
Sign up to set email alerts
|

Physics-informed learning of aerosol microphysics

Abstract: Aerosol particles play an important role in the climate system by absorbing and scattering radiation and influencing cloud properties. They are also one of the biggest sources of uncertainty for climate modeling. Many climate models do not include aerosols in sufficient detail due to computational constraints. To represent key processes, aerosol microphysical properties and processes have to be accounted for. This is done in the ECHAM-HAM (European Center for Medium-Range Weather Forecast-Hamburg-Hamburg) glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…(2022); Harder et al. (2021); Fletcher et al. (2022)), but rather to understand how the model can be simplified.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2022); Harder et al. (2021); Fletcher et al. (2022)), but rather to understand how the model can be simplified.…”
Section: Methodsmentioning
confidence: 99%
“…Note that we use the emulation merely as a tool for model analysis. Our aim is by no means to replace model components with machine learned substitutes or to replace the full model (in contrast to e.g., Arcomano et al (2022); Harder et al (2021); Fletcher et al (2022)), but rather to understand how the model can be simplified.…”
Section: Validation and Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As has been briefly touched on in previous sections, a promising and increasingly popular method for improving the performance of ML applications in weather and climate modelling is to include physics-based constraints in the ML model design (e.g. Karpatne et al, 2017;de Bézenac et al, 2017;Beucler et al, 2019;Yuval et al, 2021;Harder et al, 2022). This can be done through the overall design and formulation of the model, and through the use of custom loss functions which impose physically-motivated conservations and constraints.…”
Section: Physics Constrained ML Modelsmentioning
confidence: 99%
“…Though physical consistency is an important result by itself, imposed constraints do not necessarily improve accuracy of such tools beyond adherence to whichever physical law(s) the constraints enforce. For example, Harder et al (2022) found the accuracy of a neural network surrogate model of aerosol microphysics was not improved when adding a completion constraint during training, where a chosen variable was reassigned to the sum of all other variables' tendencies to conserve mass. However, constraints can be implemented in ways that add domain knowledge to the data-driven algorithm: Sturm and Wexler (2022) found that by adjusting a feed-forward neural network archi tecture to include a flux-tendency constraint during training, the overall prediction accuracy of chemical species concentrations improved.…”
mentioning
confidence: 99%